2018
DOI: 10.1093/jnci/djy114
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the Oligomeric Status of p53 and Clinical Outcomes in Li-Fraumeni Syndrome

Abstract: Li-Fraumeni syndrome (LFS) is a rare hereditary cancer disorder with highly variable clinical outcomes that results from germline mutations in the TP53 gene. Here we report that the quaternary structure of p53 is an important factor affecting cellular functions and the clinical outcomes of LFS patients (n = 87). Specifically, carriers of monomeric p53 mutants (n = 56) exhibited complete penetrance, with a 2.11-fold greater risk of cancer-related death (95% confidence interval [CI] = 1.07 to 4.30) and a statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 15 publications
3
28
0
Order By: Relevance
“…All data processing and statistical analyses were performed in the R statistical environment (v3.4.3), using R packages survival (v2.41-3), survminer (v0.4.1), cgdsr (v1.2.6), and miscTools (v0. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All data processing and statistical analyses were performed in the R statistical environment (v3.4.3), using R packages survival (v2.41-3), survminer (v0.4.1), cgdsr (v1.2.6), and miscTools (v0. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Methodsmentioning
confidence: 99%
“…Increasing evidence suggests that not all mutations have equally deleterious effects on p53 activity, which has been previously described as the mutant p53 functional gradient effect (14)(15)(16)(17)(18). In vitro studies demonstrate a broad range of activities when comparing different p53 mutants, where some retain near WT transcriptional activity and others are inactive (15).…”
Section: Introductionmentioning
confidence: 93%
“…While monomeric p53 TD mutants have a 100% cancer penetrance and yield a median survival time of ∼33 yr, multimeric p53 TD mutants (dimers or tetramers) exhibit a cancer penetrance of ∼80% and 51-yr median survival. Notably, monomeric mutants exhibit worse outcomes than hot spot p53 DBD mutants (penetrance: ∼90%; median survival: ∼47 yr) (Fischer et al 2018), highlighting the importance of the p53 TD in tumor suppression and the need to understand the mechanism of action of TD mutants in physiologically-relevant settings. The abnormally high cellular levels of cancer-prevalent p53 TD mutants (Rollenhagen and Chène 1998; Katz et al 2018;Park et al 2018) may confer additional activities that can contribute to disease severity and possibly explain disease outcomes.…”
Section: P53 Tetramerization Domain (Td) Mutantsmentioning
confidence: 99%
“…In collaboration with Jack Griffith, they found that human p53 C-terminal fragments interact with single stranded DNA and insertion/deletion mismatches (Lee et al, 1995). There are six critical lysines (6 K) in the C-terminal domain (CTD) of p53 (Laptenko et al, 2016) as well as critical residues for p53 function in the oligomerization domain (OD) (Fischer et al, 2016; Laptenko et al, 2016; Fischer et al, 2018). How these relate to the N-terminal region of p53 with its two transcription activation domains (AD1 and AD2) and the proline-rich (PR) region is well described (Laptenko et al, 2016) (see Figure 1, for a representation).…”
Section: The C-terminus Of Gof Mtp53mentioning
confidence: 99%